Hysteresis loops validation using hysteres program for corner beam-column joints under lateral cyclic loading - Nor Hayati, Abdul Hamid; Nurfarhana Diyana, A. H.; Haryati, Awang (IOP Publishing, 2019)
This paper presents the comparison of experimental and modelling of hysteresis loops for a corner beam-column joint under lateral cyclic loading. The beam-column joint is a sub-assemblage of a two-story precast school building. The modelled hysteresis loops were carried out using HYSTERES Program using IHYST 44 rule which is under the Ruamoko 2D folder. Modelling of hysteresis loop is one of the important processes in determining the right hysteresis model to be used in predicting the performance of the whole RC building under different level of earthquake excitations. The validation was made by determining the parameters required based on experimental loops and comparing the hysteresis loops and it response in terms of ductility, stiffness and equivalent viscous damping which obtained from both experimental and modelled hysteresis loops. It was found that the program was able to give a good agreement between them with percentage different between 2.68% and 28.49%.